Acute Hyperinsulinemia Alters Bone Turnover in Women and Men With Type 1 Diabetes. (3rd August 2020) - Sherk, Vanessa D; Vigers, Timothy; Pyle, Laura; Snell‐Bergeon, Janet K; Nadeau, Kristen J; Rickels, Michael R; Miller, Kellee M; Greenbaum, Carla J; Shah, Viral N
ABSTRACT: Type 1 diabetes (T1D) increases fracture risk across the lifespan. The low bone turnover associated with T1D is thought to be related to glycemic control, but it is unclear whether peripheral hyperinsulinemia due to dependence on exogenous insulin has an independent effect on suppressing bone turnover. The purpose of this study was to test the bone turnover marker (BTM) response to acute hyperinsulinemia. Fifty‐eight adults aged 18 to 65 years with T1D over 2 years were enrolled at seven T1D Exchange Clinic Network sites. Participants had T1D diagnosis between age 6 months to 45 years. Participants were stratified based on their residual endogenous insulin secretion measured as peak C‐peptide response to a mixed meal tolerance test. BTMs (CTX, P1NP, sclerostin [SCL], osteonectin [ON], alkaline phosphatase [ALP], osteocalcin [OCN], osteoprotegerin [OPG], osteopontin [OPN], and IGF‐1) were assessed before and at the end of a 2‐hour hyperinsulinemic‐euglycemic clamp (HEC). Baseline ON ( r = −0.30, p = .022) and OCN ( r = −0.41, p = .002) were negatively correlated with age at T1D diagnosis, but baseline BTMs were not associated with HbA1c. During the HEC, P1NP decreased significantly (−14.5 ± 44.3%; p = .020) from baseline. OCN, ON, and IGF‐1 all significantly increased (16.0 ± 13.1%, 29.7 ± 31.7%, 34.1 ± 71.2%, respectively; all p < .001) during the clamp. The increase in SCL was not significant (7.3 ± 32.9%, p = .098), but the decrease in CTX (−12.4 ± 48.9, p = .058) neared significance. ALP and OPG were not changed from baseline ( p = .23 and p = .77, respectively). Baseline ON and SCL were higher in men, but OPG was higher in women (all p ≤ .029). SCL was the only BTM that changed differently in women than men. There were no differences in baseline BTMs or change in BTMs between C‐peptide groups. Exogenous hyperinsulinemia acutely alters bone turnover, suggesting a need to determine whether strategies to promote healthy remodeling may protect bone quality in T1D. © 2020 American Society for Bone and Mineral Research © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.